Pendampingan Penulisan Artikel Hasil Penelitian Pada Jurnal Ilmiah (Kunci Sukses Mahasiswa Menulis Di Jurnal Bereputasi Nasional) - Choirudin Choirudin; M. Saidun Anwar; Agus Setiawan; Eka Fitria Ningsih; Wawan Wawan; Dian Anggraini; Mispani Mispani; Agus Purnawan; Anggi Fauziah (Edumedia Solution, 2022)
This service is in the form of mentoring activities that aim to understand students in writing accredited national scientific articles that provide the key to student success in writing in nationally reputable journals). This service activity was conducted at the Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, Indonesia. This seminar activity consists of 4 actions: presentation of material by a servant, review of scientific articles of one student by a servant, question and answer, and evaluation of service. The evaluation results of this service activity indicate that the percentage of the score in filling out the questionnaire is 90% which is in the high category, which means that this mentoring activity is very successful in providing understanding to participants in writing scientific articles. This success is due to good cooperation between the Head of Study Program, presenters from the PKM element, and students participating in this mentoring activity. The service recommends that for students to write scientific articles, students must understand three knowledge: the stages of writing, writing components of scientific papers, and submitting scientific articles to journals.